Crushing of a novel energy absorption connector with curved plate and aluminum foam as energy absorber. (February 2017) - Wang, Yonghui; Liew, J.Y. Richard; Lee, Siew Chin; Zhai, Ximei; Wang, Wei
Abstract: A novel energy absorption connector with curved plate and aluminum foam as energy absorber was developed to be inserted between a blast resistant façade and building to absorb blast energy and reduce blast load transferred to the building. Quasi-static compression loading tests were conducted to study the energy absorption performance of the proposed connectors. The crushing deformation mechanisms of the connectors were observed from the experiments and three different deformation processes were identified. The effects of aluminum foam, curved plate thickness and radius on the energy absorption performance of the connector were experimentally investigated, which showed that the energy absorption capacity of the connector could be improved by filling the connector with aluminum foam and increasing the curved plate thickness. Moreover, an analytical model was developed to predict the load–displacement curve of the energy absorption connector and the predictions from the analytical model were shown to be conservative by comparing with the experimental results. Highlights: A novel energy absorption connector inserted with aluminum foam was developed. Aluminum foam and curved plate were used for energy absorption. The energy absorption performance of the connector was experimentally studied. Analytical model was proposed to predict the load-displacement curve.